Management Visit Evaluation to Improve the Quality of Ponek Services at Bhakti Wira Tamtama Hospital Semarang - Agus Widodo; Sri Sundari (Universitas Airlangga, 2025)
Background: All hospital staff, both functional and managerial, are responsible for continuous quality improvement. Bhakti Wira Tamtama Hospital in Semarang has committed to sustainable quality improvement. This commitment is embodied in the innovative work program of the Hospital Quality and Patient Safety Committee (KMKP) of Bhakti Wira Tamtama Hospital in the form of Management Grand Rounds. This innovative work program involving management visits by the Quality and Patient Safety Committee at Bhakti Wira Tamtama Hospital has been implemented for about three years but has not been evaluated for its effectiveness. Objective: To evaluate the Management Visit in the Ponek Department of Bhakti Wira Tamtama Hospital Semarang. Methods: The type of research used in this study is a Mixed-method research design known as The Explanatory Sequential Design. Mixed Method research is a method for analyzing, collecting, and blending quantitative and qualitative research methods within a single study to understand the research problem better. Results: The Influence of Internal Factors on Staff Perception Based on the hypothesis testing results, a P-Value of 0.179. The Influence of Staff Perception on Service Quality Improvement Based on the hypothesis testing results, a P-Value of 0.000 was obtained. Conclusion: Internal factor variables have no significant influence on staff perception. There is a significant influence between the staff's perception variable regarding service quality improvement, with a correlation value of P-Value = 0.000. This result is supported by in-depth interviews that indicate positive reception by the medical staff.